MANAGEMENT OF PATENT DUCTUS ARTERIOSUS IN VERY PRETERM NEWBORNS: DO WE HAVE A PREFERENCE? - S.O. Potsiurko; D.O. Dobryanskyy; L.B. Sekretar; A.O. Menshykova; Z.V. Salabai; O.Y. Detsyk (Bukovynian State Medical University, 2019)
Introduction. Patent ductus arteriosus (PDA) is a common problem in preterm infants, which can cause complications and worsen the results of treatment. However, there is no unambiguous approach to the management of PDA. Objective. The aim of this study was to compare the efficacy of the pharmacological closure of the PDA with ibuprofen and paracetamol in premature newborns. Also, the effectiveness and feasibility of expectant management without pharmacological treatment has been evaluated. Materials and methods. 80 preterm infants (gestation age < 32 wks) with PDA diagnosed by echocardiography were enrolled into a retrospective study. Thirty of them received ibuprofen (ibuprofen group), 21 newborns were treated with paracetamol (paracetamol group), and 29 neonates were managed expectantly(comparison group).The first dose of both drugs was introduced in a median (IQR) age of 6 days (6 [1-21] days for ibuprofen and 6 [3-14] days for paracetamol; p>0.05). Results. The study groups were not different either in birth weight or in gestational age. The median(IQR) size of PDA was 3 [1.0-4.5] mm in the ibuprofen group, 2.5 [1.5-4] mm in the paracetamolgroup and 2.5 [1.0-4] in the comparison group(р<0.05), but there was no statistically significantdifferencebetween the groups in which pharmacological treatment was applied (р>0.05). Treatment with ibuprofen was effective in 27 (90%), and paracetamol - in 15 (71%) babies (p>0.05). Spontaneous closure of the PDA was observed in 21 (72%) infants from the comparison group. The median age of the babies at the time of PDA closure was 21 [6-78] days when treated with ibuprofen, 23 [8-71] days with paracetamol use, and 17 [7-48] days in the comparison group(p>0.05). 2 infants (7%) in the ibuprofen group and 3 infants (14%) in the paracetamolgroup (p> 0.05) required surgical intervention. There were no statistically significantdifferences either in the incidences of bronchopulmonary dysplasia (BPD), BPD/ death, intraventricular haemorrhage, necrotizing enterocolitis or in the length of stay and mortality rate between the groups (р>0.05). No complications connected to pharmacological treatment were seen. Conclusions. Paracetamol could be an effective and safe alternative to ibuprofen for pharmacological closure of the hemodynamically significant arterial ductus. The closure of the hemodynamically insignificant PDA can happen without pharmacological and/or surgical interventions in a 72% of very preterm infants.